Nutritional, Social, and Environmental Predictors of Scholastic and Psychosocial Outcomes in School-going Indian Adolescents: Findings from the UDAYA Study (OR32-07-19). (13th June 2019) - Scott, Samuel; Nguyen, Phuong; Pant, Anjali; Menon, Purnima
Abstract: Objectives: Adolescent wellbeing is now recognized as critical to breaking the intergenerational cycle of poverty and malnutrition. Multiple factors shape cognitive wellbeing during adolescence, thus we sought to take a holistic approach in examining factors related to mental outcomes among Indian adolescents. Methods: Data were drawn from in-school adolescents aged 10–19 years ( n = 2482 females (F), 2728 males (M)) in the Understanding the Lives of Adolescents and Young Adults (UDAYA) study in Uttar Pradesh and Bihar, India. We examined four outcomes: literacy, numeracy, aspiration for advanced studies, and depression. Predictors spanned nutritional factors (anemia, underweight, dietary diversity, free school meals), social support (number of friends, time spent with friends, parental support, substance abuse, household violence), and environment (urban, sanitation, household wealth, school quality, work outside school). Mutually-adjusted logistic regression models, accounting for cluster sampling design and state fixed effects, were used to examine associations between these predictors and the four outcomes for M and F separately. Results: Among nutritional factors, associations were found between anemia and depression (F: AOR 1.40, 95% CI 1.00–1.97), underweight and numeracy (M: 0.72, 0.54–0.96), dietary diversity and literacy (F: 1.09, 1.01–1.17). Receiving free school meals was associated with poorer outcomes (AORs 0.37 to 0.50), which we attribute to the pro-poor program targeting. Strong parental support was related to higher literacy (M: 4.66, 2.89–7.54), numeracy (M: 2.64, 1.64–4.26; F: 1.70, 1.07–2.70) and aspirations (M: 1.84, 1.25–2.69) while substance abuse and violence were related to worse outcomes (AORs 0.56 to 0.72). Higher wealth predicted higher literacy, numeracy and aspirations. Having an improved latrine facility at home predicted higher numeracy (F: 1.60, 1.11–2.30) and aspirations (F: 1.87, 1.28–2.75). Conclusions: Our findings highlight the complexity of factors that adolescents face which affect their mental wellbeing. Policies and programs to improve adolescent mental health require well-rounded packages of interventions targeting nutritional, social, and environmental aspects of life. Funding Sources: Bill & Melinda Gates Foundation through POSHAN, led by IFPRI.